Determination of microbiological quality and histamine levels in rainbow trouts (Oncorhynchus mykiss) - AKSOY, A; SEZER, Ç; ATASEVER, M; ÇETINKAYA, A; GÜLBAZ, G (Journal of the Hellenic Veterinary Medical Society, 2022)
This study aims to determine the microbiological quality and histamine levels of fresh-marketed rainbow trouts (Oncorhynchus mykiss). The total mesophilic aerobic bacteria (TMAB), total psychrophilic aerobic bacteria (TPAB), coliform, fecal coliform, Enterobacteriaceae, Pseudomonas, Staphylococcus-Micrococcus and mold-yeast numbers were detected as 4.24, 4.00, 1.10, 0.17, 1.50, 3.05, 0.28 and 3.82 log10 cfu/g, respectively. Yersinia enterocolitica, Listeria monocytogenes, Escherichia coli O157:H7 and Vibrio spp bacteria were found in 18 (37.5%), 14 (29.1%), 8 (16.6%) and 14 (29.1%) respectively. Twenty-eight out of 51 Listeria isolates (54.9%) were verified through PCR analysis as L. monocytogenes. It was determined that the histamine level in the samples was above the detectable level (>2.5 mg/kg) in 8 of the samples (16.6%)determined using an ELISA method. It was concluded that the detection of foodborne pathogens in fresh-marketed fish samples potentially constitutes a public health hazard.